THE EFFECT OF CYBERLOAFING ON PERFORMANCE MODERATED BY WORK PROCEDURES AND SELF-CONTROL - Rahmawati M. Hatala; Anang Kistyanto; Andre Dwijanto Witjaksono (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
In today's digital era, cyberloafing which refers to surfing the web for personal reasons during work hours is a major workplace issue. A policy was put in place at XYZ Agency in July 2024 to control internet usage and curb cyberloafing. The policy is meant to boost productivity, but its impact is still uncertain. Even with the policy, some employees continue cyberloafing on personal internet connections, leading to concerns about its effect on their work performance and how self-control and work procedures play a role in this behavior. This study seeks to investigate the impact of cyberloafing on productivity, influenced by levels of self-discipline and workplace protocols. Employing a quantitative method, the research involved 100 participants from the XYZ Agency. Utilizing Smart PLS 3.0 software, the data was examined to ascertain connections between different factors. The results indicated that cyberloafing had a notable, albeit modest, positive effect on performance measures within this study, with a coefficient of 0.161. Workplace procedures, acting as a moderating element, were found to have a detrimental impact on the correlation between cyberloafing and employee productivity. However, self-control was not found to significantly alter or moderate the link between cyberloafing and job performance.